Advantages and Disadvantages of Vein-Venous Bypass during Liver Transplantation - S. V. Zhuravel; A. O. Chugunov; K. N. Lutsyk; V. Kh. Timerbayev; A. V. Chzhao (Общая реаниматология, 2008)
Objective: to study the advantages and disadvantages of vein-venous bypass (VVB) used during liver transplantation. Subjects and methods. Fifty patients who had undergone orthotopic liver transplantation (OLT) were examined. OLT was performed without using VVB in Group 1 (n=25). In Group 2 (n=25) of OLT, during an anhepatic period (the interval of the cessation of blood flow along the inferior vena cava to the reperfusion of the implanted donor liver with venous blood), blood return was accomplished by compulsory porto-femoroaxillary shunting by means of a centrifugal pump. Results. The persistent perfusion pressure provided by VVB prolongs an anhepatic period; moreover, the functions of the kidney and heart remain stable. At the same time the longer time of an anhepatic period increases the time of cold ischemia of the grafted liver. VVB with a heat exchanger can warm a patient to normal temperature over a short period of time. Moreover, the decrease in a patient’s body temperature without using VVB is 0.5—1.5° from the start of an operation to the time of venous hepatic reperfusion. The authors failed to record intraoperative mortality from heart failure in the examinees. There were no differences in the incidence of renal dysfunction with and without VVB. Conclusion. The number of complications and the outcome of an operation do not depend on whether VVB is used or not. Liver transplantation without VVB makes it possible to reduce the time of surgery, an anhepatic period and the cost of a surgical intervention. During each liver transplantation, VVB must be linked up due to the fact that circulation can fully stop in the inferior vena cava at the stage of hepatectomy. Key words: liver transplantation, vein-venous bypass.